Prevalence of HPV infection and cervical intraepithelial lesions in HIV positive and negative women in the city of Florianopolis - Coradeschi , Pâmela Raquel (2023)
Introduction: HPV infection is the most frequent sexually transmitted infection in women. The high oncogenic risk HPV, associated with others factors, there are a risk of progressing to a precancerous lesion of the cervix and even cancer. This evolution is related to the persistence of the infection and other factors, mainly those that interfere with the woman's immunity. The immunosuppression caused by HIV infection is an important factor for viral persistence and the appearance of these lesions. Objectives: To compare the prevalence of HPV infection and cervical intraepithelial lesions in HIV-positive and negative women and describe the possible associated risk factors. Methods: The sample consisted of 50 HIV positive women (study group) and 50 HIV negative women (control group) recruited from the public health system of Florianópolis during the months of January to April 2022. Cervical samples were collected for cytological analysis and for detection of high-risk oncogenic HPV DNA by polymerase chain reaction (PCR). Categorical variables were compared using the chi-square test, with a significance level set at 5% Results: HPV infection was more prevalent in the control group, however, HIV positive women had a higher frequency of intraepithelial lesions diagnosed on cytology. Factors such as greater number of sexual partners, depression and smoking were more frequent in the group of HIV positive women. The number of CD4 T cells less than 200 cels/mm3 was associated with a higher number of altered Pap smears and a positive HPV DNA test. The use of combination antiretroviral therapy and undetectable viral load were associated with a greater number of normal cytology and undetected HPV DNA. Conclusion: The prevalence of cervical intraepithelial lesions in HIV-infected women is higher than in women without infection. The presence of HIV infection was the most important risk factor associated with the development of cervical lesions.